Postmortem human brain genomics in neuropsychiatric disorders — how far can we go?. (February 2016) - Jaffe, Andrew E
Highlights: Large collections of human brain tissue are prevalent in neuropsychiatric research. Analyzing genes and their networks in the human brain can inform etiology. Cellular composition should be considered in studies of homogenate brain tissue. Methods for isolating cell populations can be powerful tools but come with caveats. Abstract : Large-scale collection of postmortem human brain tissue and subsequent genomic data generation has become a useful approach for better identifying etiological factors contributing to neuropsychiatric disorders. In particular, studying genetic risk variants in non-psychiatric controls can identify biological mechanisms of risk free from confounding factors related to epiphenomena of illness. While the field has begun moving towards cell type-specific analyses, homogenate brain tissue with accompanying cellular profiles, can still identify useful hypotheses for more focused experiments, particularly when the dysregulated cell types are unknown. Technological advances, larger sample sizes, and focused research questions can continue to further leverage postmortem human brain research to better identify and understand the molecular etiology of neuropsychiatric disorders.